"Race or People": Federal Race Classifications for Europeans in America, 1898-1913 - Joel Perlmann (Levy Economics Institute of Bard College, 2001)
In this paper, I follow the development of the classification scheme discussions closely through its formative decade, from the last years of the 1890s through about 1913, by which time three revealing publications close the prewar developments: the United States Immigration Commission's massive Reports , including its volume 5, The Dictionary of Races and Peoples; the critique of the Reports by I. A. Hourwich in Immigration and Labor and the publication of the Census Bureau reports on mother tongue in the 1910 enumeration.
Keywords: 330; Rasse; Migranten; Klassifikation; Geschichte; USA